322 Effects of Feeding High Protein Distillers Dried Grains (HP-DDG) on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs. (10th April 2018) - Yang, Z; Urriola, P E; Zeng, Z K; Hilbrands, A M; Johnston, L J; Shurson, G C
Abstract: High protein distillers dried grains (HP-DDG) previously produced from front-end fractionation processes had different nutrient composition than HP-DDG currently being produced using new technologies (ICM, Inc., Colwich, KS). The objective of this study was to test the hypothesis that using previously published estimates for ME, standardized ileal digestible (SID) of AA, and standardized total tract digestibility (STTD) of P supports acceptable growth performance and carcass composition of growing-finishing pigs fed diets containing 30% new generation HP-DDG. Mixed sex growing-finishing pigs (n = 144; initial BW = 22.7 ± 2.3 kg) were blocked by BW and sex in a randomized complete block design and allotted to 1 of 2 treatments (9 pigs/pen, 8 pens/treatment). Dietary treatments consisted of corn-soybean meal control diets (CON) and diets containing 30% HP-DDG using a 4-phase feeding program over a 16-wk period. Within each phase, diets were formulated to contain equal SID Lys:ME and STTD P using published ME and digestibility values for HP-DDG from NRC (2012), which were derived from HP-DDG produced previously from front-end fractionation processes. Overall, pigs fed HP-DDG had reduced ( P < 0.01) final BW (126.6 kg vs. 133.4 kg, SEM = 1.2; P < 0.01) and ADG (0.95 kg/d vs. 1.01 kg/d, SEM = 0.01) compared with pigs fed CON, but no there were no differences in ADFI or G:F between treatments. Pig fed HP-DDG diets had reduced HCW (93.4 kg vs. 100.8 kg, SEM = 1.3; P < 0.05), carcass yield (73.8% vs. 75.6%, SEM = 0.3; P < 0.01), LM area (42.7 cm 2 vs. 47.5 cm 2, SEM = 0.7; P < 0.05), and backfat depth (21.3 mm vs. 22.3 mm, SEM = 0.4; P < 0.01) compared with pigs fed CON, but percentage of carcass fat-free lean was unaffected by treatment. Pigs fed HP-DDG had less ( P < 0.01) SFA (34.7% vs. 39.6%, SEM = 0.9) and MUFA (39.6% vs. 43.5%, SEM = 0.7) content in backfat than pigs fed CON, while PUFA content (21.5% vs. 12.1%, SEM = 0.8) and iodine value (70.0 vs. 57.7, SEM =1.2) were greater ( P < 0.01) than those fed CON. These results suggest that SID AA content of new generation HP-DDG were likely overestimated in diet formulation and resulted in reduced ADG, BW, and subsequent HCW, and LM area. More accurate digestibility coefficients are needed to achieve optimal growth performance when feeding new generation HP-DDG to growing-finishing pigs.